Hoarding Symptoms Are Not Exclusive to Hoarders - Novara, Caterina; Bottesi, Gioia; Dorz, Stella; Sanavio, Ezio (Frontiers in Psychology, 2016)
Hoarding Disorder (HD) was originally conceptualized as a subcategory of Obsessive Compulsive Disorder (OCD), and numerous studies have in fact focused exclusively on investigating the comorbidity between OCD and HD. Hoarding behavior can nevertheless also be found in other clinical populations and in particular in patients with eating disorders (ED), anxiety disorders (AD), major depression (MD), and psychotic disorders (PD). The current study was carried out with the aim of investigating, using a validated instrument such as the Saving Inventory-Revised (SI-R), the presence of HD symptoms in patients diagnosed with ED, AD, MD and PD. Hoarding symptomatology was also assessed in groups of self-identified hoarders (SIH) and healthy controls. The results revealed that 22.5% of the ED patients exceeded the cut-off for the diagnosis of HD, followed by 7.7% of the patients with MD, 7.4% of the patients with AD, and 5.9% of the patients with PD. The patients with ED had significantly higher SI-R scores than the other groups in the Acquisition and Difficulty Discarding scales while the AD, MD, and PD patients were characterized exclusively by Difficulty Discarding. These data suggest to clinicians that hoarding symptoms should be assessed in other types of patients and especially in those affected by Bulimia and Binge eating.